2015
DOI: 10.1002/adma.201501592
|View full text |Cite
|
Sign up to set email alerts
|

Performance Enhancement of Electronic and Energy Devices via Block Copolymer Self‐Assembly

Abstract: The use of self-assembled block copolymers (BCPs) for the fabrication of electronic and energy devices has received a tremendous amount of attention as a non-traditional approach to patterning integrated circuit elements at nanometer dimensions and densities inaccessible to traditional lithography techniques. The exquisite control over the dimensional features of the self-assembled nanostructures (i.e., shape, size, and periodicity) is one of the most attractive properties of BCP self-assembly. Harmonic spatia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
63
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 95 publications
(63 citation statements)
references
References 158 publications
(239 reference statements)
0
63
0
Order By: Relevance
“…The two main members of the nanogenerator family used for harvesting mechanical energy from the environment are piezoelectric NG (PENG) 71 and triboelectric NG (TENG) 72 . Out of these two TENG has been proved to be very promising for harvesting mechanical energy from water [73][74][75][76] wind 77, 78 motion of humans [79][80][81] .The outstanding energy harvesting capabilities of both PENG and TENG have garnered worldwide attention from researchers and industries. Further research and innovations of NGs will mark the NANOTECHNOLOGY FOR ACHIEVING GREEN-ECONOMY Garima Pandey development of self-powered systems which will lead to a promising future of energy and sensing technology.…”
Section: Nanotechnology In Energymentioning
confidence: 99%
See 1 more Smart Citation
“…The two main members of the nanogenerator family used for harvesting mechanical energy from the environment are piezoelectric NG (PENG) 71 and triboelectric NG (TENG) 72 . Out of these two TENG has been proved to be very promising for harvesting mechanical energy from water [73][74][75][76] wind 77, 78 motion of humans [79][80][81] .The outstanding energy harvesting capabilities of both PENG and TENG have garnered worldwide attention from researchers and industries. Further research and innovations of NGs will mark the NANOTECHNOLOGY FOR ACHIEVING GREEN-ECONOMY Garima Pandey development of self-powered systems which will lead to a promising future of energy and sensing technology.…”
Section: Nanotechnology In Energymentioning
confidence: 99%
“…Though the efficiency of these cells is not enough when compared with silicon solar-cells still the use of quantum dot nanostructures improves their efficiency because their wide band-gap makes them absorb a broad spectrum of EMR.CNMs like C60-fullerenes 91,92 graphenes and 93, 94 C-nanotubes 95,96 have been found to be tremendously competent electron acceptors for use in quantum dot and polymer solar cells 97 . The energy conversion and transfer efficiency of dye-sensitized solar cells can be improved by using nano-crystalline film of charge transfer dye coated mesoporous TiO2(titanium dioxide) on a transparent charge conducting substrate [73][74][75][76] .The affluent surface chemistry, large surface area, and low specific-densities of nanoporous metallic make them extremely useful as very proficient electro-catalysts in fuel cells 80,81 .Though platinum nanoparticles based electrodes show carbon mono-oxide deactivation and sometimes dependent drifting nature ,still the great resistance and higher electro-catalytic activities of 97,98 nanosized bi and trimetallic alloys of platinum have shown promising results as good cell catalyst 99 .While the new generation photovoltaic cells like polymer cells, multi-junction solar cells, thin-film chalco-genides, hybrid perovskites, quantum dot-based solar cells have shown promising future of green economy still, to make them broadly accepted and marketed, there are many issues that need to be addressed and resolved. The distribution of electrical energy generated from renewable resources requires proper storage mediums ranging from huge public efficacies to pocket-sized handy electronic machines which are being achieved by using batteries as a chemical medium of storage or electrical capacitors as capacitive storage 100,101 .…”
Section: Nanomaterials For Energy Conversion and Storagementioning
confidence: 99%
“…BCPs can form various microphase separated nanostructures [12]. The self-assembly of block copolymers is a promising platform for the fabrication of nanostructured materials and devices [13][14][15][16][17][18][19][20]. We previously reported that BCPs can be hierarchically structured by combining phase separation with laser interference ablation [10].…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, many researchers have shown interest in block copolymers during the last decade [5][6][7]. Block copolymers can self-assemble into different nanostructures that depend on several parameters such as copolymer composition (f), Flory-Huggins interaction parameter among both blocks (χ), and polymerization degree of the copolymer (N).…”
Section: Introductionmentioning
confidence: 99%